2016
DOI: 10.1039/c6cp01287f
|View full text |Cite
|
Sign up to set email alerts
|

Methane adsorption and dissociation on iron oxide oxygen carriers: the role of oxygen vacancies

Abstract: We performed ab initio DFT+U calculations to explore the interaction between methane and iron oxide oxygen carriers for chemical looping reaction systems. The adsorption of CH4 and CHx (x = 0-3) radicals on α-Fe2O3(001), and the influence of oxygen vacancies at the top surface and on the subsurface on the adsorption properties of the radicals was investigated. The adsorption strength for CH4 and C radicals at the top of the α-Fe2O3(001) surface in the presence of oxygen vacancies is lower than that on the stoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 59 publications
(100 reference statements)
1
57
0
Order By: Relevance
“…7. The data of the previous computational study on CH 4 adsorption on Fe 2 O 3 (001) surface are given by the filled circle 21 . It can be seen that CH 4 adsorption energies dramatically decrease with increasing number, n when the sizes of Fe 2 O 3 nanoparticles are at a relatively small scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7. The data of the previous computational study on CH 4 adsorption on Fe 2 O 3 (001) surface are given by the filled circle 21 . It can be seen that CH 4 adsorption energies dramatically decrease with increasing number, n when the sizes of Fe 2 O 3 nanoparticles are at a relatively small scale.…”
Section: Resultsmentioning
confidence: 99%
“…The formed CO may further react with surface lattice O atoms to form CO 2 21,22 . For the Fe 40 O 60 nanoparticle, the formation of CO 2 needs to overcome a barrier of 148.9 kJ mol −1 , which is 30.4 kJ mol −1 higher than that of CO 2 formation on Fe 2 O 3 (001) surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that oxygen vacancies is doomed to form as OCs donate lattice oxygen during the reduction of CLR, it was therefore important to decern their effect on the interaction between methane and Fe‐based OCs. It was reported that different oxygen vacancies on the surface had distinct influence on the adsorption strength for CH x (x=0–4) radicals [33] . That is, adsorption strength for CH 4 and C radicals at the top of the α‐Fe 2 O 3 (001) surface in the presence of oxygen vacancies was lower than that on the stoichiometric surface while it was correspondingly higher for CH x (x=1–3) radicals, but oxygen vacancy formation on the subsurface significantly increased that of CH x (x=0–3) radicals.…”
Section: Oxygen Carriersmentioning
confidence: 99%
“…DFT calculations revealed the role of oxygen vacancy concentrations in modulating the oxygen diffusion rate. Specifically, a high oxygen vacancy concentration can lead to a low oxygen diffusion energy barrier and oxidize the carbon deposition in time [34].…”
Section: Introductionmentioning
confidence: 99%